ENERGI IMPAK HELMET SEPEDA MOTOR YANG DIKENAI BEBAN JATUH BEBAS - Simanjuntak, Rahmat Kartolo (JURNAL ILMU PENGETAHUAN DAN TEKNOLOGI TERAPAN "REINTEK" (REKAYASA INOVASI TEKNOLOGI), 2012)
Events that often occur in traffic accidents where the driver i s falling from the vehicle and the clash of heads in spite of wearing a motorcycle helmet, but the type of non-standard helmet. From these events we need to know how much impact energy received at the impact location that causes damage to the helmet. This study aims to obtain the variation of impact energy that was absorbed by motorcycle helmet to the height of fall and form the anvil. The method used in this study is in free fall impact method using free-fall impact tester multipurpose. Testing is done by giving the variation of the height of fall and forms the basis of testÂ  ( anvil) . The test result on several types of anvil was found that the smallest energy that causes the damage occurred on helmet bullet type anvil, amounting to 3.24 J at a height of 0.3 m. This means that by using only a very small energy, the motorcycle helmet will fail. While on a flat plate type anvil energy required to cause failure on a motorcycle helmet is 16.50 J at a height of 0.75 m.